Comparative Study of Particulate Matter (PM) Emissions in Diesel Engine Using Diesel-Methanol Blends - Ahmad Fitri, Yusop; R., Mamat; Mohd Hafizil, Mat Yasin; Abdul Adam, Abdullah; Amir, Aziz (Trans Tech Publications Inc., 2014)
In this research, Palm Oil Methyl Ester (PME) was added to methanol-biodiesel fuel in order to reduce the emissions. Thus, for diesel engines, alcohols are receiving increasing attention because they are oxygenated and renewable fuels. Therefore, in this study, the effect of PM emission level of a four cylinder, naturally aspirated, indirect injection diesel engine has been experimentally investigated by using methanol-blended diesel fuel from 0% to 20% with an increment of 5%. Thus, the effects of methanol on particulate matter (PM) components, soluble organic fraction (SOF) and dry soot (DS) using different type of fuel blends were investigated. Using a composite filter, the ester-methanol-diesel characteristic such as mass concentration in term PM, SOF and DS were analyzed under different engine operating conditions. The results show that the combination of 10% of methanol with 20% of Palm Oil Methyl Ester gives less PM emissions. Thus, PME20M10 of methanol-biodiesel fuel can reduce the PM emissions effectively for all load condition.